KULEKO Vertical Axis Wind Turbines - Mammadova, Nigar (ADA University, 2021)
The government of Azerbaijan has prioritized the development of renewable and alternative energies as a key area and has already established governmental entities in charge of alternative and renewable energy sources. Today, natural gas provides a significant amount of Azerbaijan's electricity. Successful project implementation will contribute to the greening of Azerbaijan's economy and create the ability for a gradual shift toward a low-carbon development model. Azerbaijan is a country with enormous potential for renewable energy growth due to its outstanding wind resources, particularly along the Caspian Sea's shore. Given that oil and gas exports constitute the backbone of Azerbaijan's economy, diversification into renewable energy can function as a catalyst for new job possibilities in a country, providing a foundation for technological innovation and opening up new sectors for economic value creation and GDP growth. Furthermore, the use of alternative energy, together with long-term improvements in energy efficiency, has the potential to reduce domestic consumption of oil and gas while also providing prospects for additional money from exports. Around the last few decades, not only in Azerbaijan, but all over the world, there has been a surge in demand for power and electrification of transportation. The purpose of this paper is to investigate the feasibility and business development plan for small scale vertical axis wind turbines in Azerbaijan with potential for entry to CIS region in future. The introduction section of the thesis will provide the context of this study, highlighting the reasons for selecting this startup venture and which problems does product address. There will also be a brief discussion of the climate in which the wind energy business is evolving, competitive environment, as well as the problems and possibilities that it may face in the future. Taking current trends and research into consideration, developing such a business venture/startup can be advantageous in terms of strategic view of the country and obtaining genuine investment in case of project execution in the future.
Keywords: Business; Renewable energy.; Greentech.; Alternative energy.